(3TQM CUhd EYJbGO Cgd GdSfI hGdLeGYI ef GdcJGH hGdSfIs - (3GddGdcGFj , gHI Gddg Hf GdMSf Hf efUhQ GdWHQj GdQGRj, CHh GdbGSe,J (B418 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CXgQ GdMb hChVMg hcTa Yf SHjdg hHjfg heG cda Gddg YHGOg ef age JhMjOg hUaGJg s
(3BNQgG (B:s
(3jfJgi HGdcdGe Ydi bhdg JYGdi (B( (3heG NdbJ GdLf hGdEfS EdG djYHOhf (B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B71 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B136s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(1338) s
Keywords: (3GdJhMjO hGdedd hGdfMds